Mapping the Future Skills: A Training Needs Analysis of Education Support Staff in a Vocational Faculty - Abdul Hafidz; Warju Warju; Yuni Lestari; Fajar Indra Kusuma; Mafrur Udhif Nofaizzi; Tri Wardati Khusniyah (Vokasi UNESA Bulletin of Engineering, Technology and Applied Science, 2025)
Educational staff, commonly referred to as administrative human resources, play a critical role as strategic assets in supporting the success of higher education institutions, including at the Vocational Faculty of Surabaya State University (Unesa). Institutional performance and service quality are closely linked to the competence and performance of these educational staff. Therefore, systematic training and development efforts are essential to enhance their competencies in line with the dynamic needs of the institution. One effective approach to designing relevant and impactful training programs is through Training Needs Assessment (TNA), which serves as a critical initial step in the training design process. TNA helps to identify gaps between existing competencies and future institutional demands, ensuring that training programs are targeted, responsive, and aligned with both institutional strategic objectives and individual performance improvement. This study aims to design a comprehensive training and development model for educational staff at the Vocational Faculty of Surabaya State University, based on a structured TNA process. The TNA will adopt both macro and micro approaches, mapping institutional-level needs as well as job-specific and individual performance gaps. The expected output is the development of an up-to-date, data-driven training and development model that can serve as a strategic reference for preparing faculty development plans and academic texts in the future, ensuring the sustainable improvement of educational staff competencies and institutional performance